Development of plant-based burger patties with pea protein isolate and barnyard millet flour and its storage stability in aerobic and vacuum packaging - Neo, Cynthia Wen Xuan; How, Yu Hsuan; Kong, Ianne; A. Talib, Rosnita; Pui, Liew Phing (John Wiley and Sons Inc, 2024)
There is an increasing demand for plant-based burger patties owing to the health and sustainability issues raised from the consumption of meat. This study aimed to develop plant-based burger patties from pea protein isolates (PPIs) and barnyard millet flour (BMF) through high-moisture extrusion cooking. The extrudates for plant-based burger patties were developed with a blend ratio of 90:10 PPIs:BMF with different screw speeds ranging from 40 to 120 rpm. The extrudates produced with different screw speeds were analyzed, followed by the analysis of the plant-based burger patties. Commercial plant-based burger patties were used as a control. The optimized plant-based burger patties were then stored in aerobic or vacuum packaging for 12 days under refrigerated condition and analyzed. The optimized extrudates produced using screw speed of 80 rpm displayed moderate water absorption index (3.33%), high hardness (4143–4390 g), and high adhesion (0.47 mJ). The plant-based burger patties produced using the optimized extrudates had 2006–2608-g hardness, 0.17 cohesiveness, and 6.70% cooking loss. In comparison to aerobic packaging, the plant-based burger patties stored in vacuum packaging demonstrated lower cooking loss (8.46%), moisture content (18.03%), total color difference (3.02), and total plate count (8.65 log10 cfu/g) after 12 days of refrigerated storage. The protein content of plant-based burger patties was not affected throughout the refrigerated storage. This shows the potential of PPIs and BMF mixtures as meat analogue ingredients and the suitability of vacuum packaging for the storage of plant-based meat.